The Influence of the Shadow Economy and Corruption on Public Debt in European Union Countries pre and post Covid-19 - Asmaa El-Naser (Ovidius University Annals: Economic Sciences Series)
This study aims to analyze the influence of the shadow economy and corruption on public debt in EU countries pre- and post-COVID-19, during 2003-2021, focusing on the challenges arising from recovery efforts after the COVID-19 pandemic. Using the GMM model, the results indicate that the informal economy has a negative impact on public debt in most models, while corruption increases the accumulation of debt. GDP per capita also negatively impacts debt, while unemployment rates are positively associated with an increase in debt due to social expenditures. Inflation and investment negatively impact debt, while population growth and trade exhibit complex effects. The study recommends stimulating the transition to the formal economy, improving transparency and combating corruption, enhancing economic growth, controlling inflation, supporting public investment, and promoting international trade to address public debt challenges.